PENERAPAN PENGGUNAAN MEDIA POHON AKSARA DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DI KELAS 1 SISWA SD NEGERI 1 NGINGIT - Nurul Octavia; Denna Delawanti Chrisyarani; Dwi Agus Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Beginning reading ability is a fundamental skill that must be mastered by first-grade elementary school students, as it serves as the foundation for future academic success. However, early reading instruction is still predominantly implemented using conventional methods that tend to be monotonous and less engaging, resulting in low reading proficiency among students. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of four stages: planning, acting, observing, and reflecting. The research subjects were 28 first-grade students of SD Negeri 1 Ngingit in the first semester of the 2025/2026 academic year. The study was conducted in two cycles, each consisting of two meetings. The results showed a significant improvement in students’ beginning reading abilities. In the pre-cycle stage, only 21.43% of students were categorized as fluent readers. After the implementation of the Pohon Aksara media in Cycle I, the percentage increased to 42.86%, and further improved significantly to 82.14% in Cycle II. The Pohon Aksara media is recommended as an effective alternative instructional medium to enhance early literacy in lower-grade elementary school classrooms.